Determinants of bank profitability in a developing economy: empirical evidence from the Philippines - Sufian, Fadzlan; Razali Chong, Royfaizal (Asian Academy of Management (AAM) and Penerbit Universiti Sains Malaysia, 2008)
The present paper seeks to examine the determinants of Philippines banks profitability during the period 1990–2005. The empirical findings suggest that all the bank-specific determinant variables have a statistically significantly impact on bank profitability. The empirical findings suggest that size, credit risk, and expense preference behaviour are negatively related to banks' profitability, while non-interest income and capitalisation have a positive impact. During the period under study, the results suggest that inflation has a negative impact on bank profitability, while the impact of economic growth, money supply, and stock market capitalisation have not significantly explained the variations in the profitability of the Philippines banks.